2013
DOI: 10.1093/comjnl/bxt017
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Impact of Server Virtualization on Energy Efficiency for Green Data Center

Abstract: The swift adoption of cloud services is accelerating the deployment of data centers. These data centers are consuming a large amount of energy, which is expected to grow dramatically under the existing technological trends. Therefore, research efforts are in great need to architect green data centers with better energy efficiency. The most prominent approach is the consolidation enabled by virtualization. However, little effort has been paid to the potential overhead in energy usage and the throughput reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…IaaS CMSs, such as OpenStack [8], use VMs to partition a cluster, run one DCS per partition, and let each DCS to manage and schedule submitted applications [11].…”
Section: B Related Work: Cluster Management Systemsmentioning
confidence: 99%
“…IaaS CMSs, such as OpenStack [8], use VMs to partition a cluster, run one DCS per partition, and let each DCS to manage and schedule submitted applications [11].…”
Section: B Related Work: Cluster Management Systemsmentioning
confidence: 99%
“…Among them, CPU plays the most important role in power consumption. Specially, [15,16,18] has observed a linear relationship between CPU utilization and power consumption. Moreover, several studies and experiments have found that an idle server consumes about 60 % of the peak power [12].…”
Section: Energy Modelmentioning
confidence: 99%
“…Among those impacting factors, CPU plays the most important role in power consumption. Specially, [11], [12] has observed a linear relationship between CPU utilization and power consumption. Moreover, several studies and experiments have found that an idle server consumes about 60% of the peak power [13].…”
Section: Energy Modelmentioning
confidence: 99%